2020
DOI: 10.1128/jvi.01486-20
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly Effective Priming of CD8+T Cells by Heat-Inactivated Vaccinia Virus Virions

Abstract: Robust priming of CD8+ T cells by viruses is considered to require infection and de novo expression of viral antigens. A corollary of this is that inactivated viruses are thought of as being inevitably poor vaccines for eliciting these responses. Contrary to this dogma we found that some antigens present in vaccinia virus (VACV) virions prime strong CD8+ T cell responses when the virus was rendered non-infectious by heat. More surprisingly, in some cases these responses were similar in magnitude to those prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Finally, we wanted to show that CPXV12 + 203 do not impede the supply of antigen from infected cells for cross priming by DCs. To do this, we used a well-characterized in vivo cross priming experiment in which MHC-mismatched cells were infected with MVA or M-CPX12 + 203 in vitro and then heated to inactivate residual virus before being used to immunize mice ( 17 , 19 , 38 ). We then examined CD8 + T cell responses to a set of VACV epitopes that can be cross primed in this setting ( 17 , 38 ) and found that cells infected with either virus elicited a similar-sized response to all specificities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we wanted to show that CPXV12 + 203 do not impede the supply of antigen from infected cells for cross priming by DCs. To do this, we used a well-characterized in vivo cross priming experiment in which MHC-mismatched cells were infected with MVA or M-CPX12 + 203 in vitro and then heated to inactivate residual virus before being used to immunize mice ( 17 , 19 , 38 ). We then examined CD8 + T cell responses to a set of VACV epitopes that can be cross primed in this setting ( 17 , 38 ) and found that cells infected with either virus elicited a similar-sized response to all specificities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the nature of antigen has a significant impact on T cell-mediated immunity 58 . Inactivated whole-virion vaccines provide a complex antigenic structure which enhances antigen presentation and T cell responses 59 . Even though there is no consensus in the literature, alum can also positively influence DC maturation and/or increase the costimulatory signals for T cell-mediated immunity 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, vMC021L-HA induced strong T CD8+ responses, a hallmark of VACV that spreads effectively [76]. However, immunization with inactivated VACV virions can induce an effective T CD8+ response [81], so it is possible that the production of EV by cells infected at the site of immunization produces sufficient virus particles to reproduce, or even PLOS PATHOGENS exceed this immunogenicity. In addition, when one considers the increased immune response generated by vMC021L-HA compared to vΔF13L, it seems likely that the slight increase in spread (Fig 3) may have been enough to elicit a robust immune response.…”
Section: Discussionmentioning
confidence: 99%